Measuring the Smart Growth Spatial Performance in Developing City of Northwest China Plains Area - Jing Li; Hongwei Zhou; Zhongyuan Cai (Geofluids, 2021)
“Smart growth” is an urban planning concept. In this paper, the overall urban-rural smart growth efficiency is explored, which serves as an indicator to effectively measure the allocation of urban-rural spatial resources and structural rationality of the urban-rural space. Taking a developing county city in northwest China plains area as an example, the urban-rural spatial efficiency system was established and the evaluation model constructed by using the data envelopment analysis (DEA)-slack-based measure (SBM) model. The model was used to empirically analyze the characteristics in 2000, 2010, and 2018. The results show that the urban-rural spatial efficiency of the urban-rural space degree of a county in northwest China plains area exhibits growth trend on the whole, and scale efficiency increases the most. The increase of technical efficiency promotes the growth of spatial performance, which is mainly manifested in the construction of industrial parks. Although urban and rural spatial performance has made great achievements, there are still problems. Results of the test for each city indicate that the method proposed in this study is, in fact, quite effective in evaluating the smart growth pattern for developing cities. Finally, the corresponding improvement social and economic policies’ strategy is proposed.